(untitled) - Chaim Gutfinger (New York, 1997)
The book presents the fundamentals of modern fluid mechanics, including hydrostatics, viscous flow, similitude and order of magnitude, creeping flow, potential flow, boundary layer flow, turbulent flow, compressible flow, and non-Newtonian fluids
Keywords: fluid mechanics